Subutilization of COPD Guidelines in Primary Care - Rafael Laniado-Laborín; Adrian Rendón; Juan Manuel Alcantar-Schramm; Rebeca Cazares-Adame; Otto Bauerle (SAGE Publishing, 2013)
Summary: Despite the popularity of chronic obstructive pulmonary disease (COPD) guidelines, studies have reported important deficits among primary care physicians (PCPs) with respect to diagnosis and treatment of COPD; as a consequence, COPD remains underrecognized and undertreated. Methods: This was a multicenter pilot study to assess prescribing practices for COPD by PCPs according to COPD guidelines. This was a 2-phase study: In phase 1, PCPs from 27 Mexican cities, referred patients for evaluation, including spirometry and in phase 2, PCPs from 10 of those same cities were asked to answer a questionnaire on COPD practice guidelines. Results: A total of 2293 subjects were included in phase 1; 472 (20.6%) had a FEV 1 /FVC <70%. Only 39% of patients with 30% ≤ FEV 1 < 50% and 22% with FEV 1 <30% were receiving combination therapy (long-acting bronchodilator + inhaled steroid). In phase 2, we recruited 999 PCPs; 72.5% of them said that they had read a COPD guideline and 59.4% answered that they used one in their practice. When asked which guideline(s) they used, we had 86 different responses with GOLD (Global Initiative for Chronic Obstructive Lung Disease; 34.1%) being the most common, followed by GINA (Global Initiative for Asthma; 12.8%). When asked why they did not used a guideline, we got 33 different answers; "never read them" was the most frequent answer (41.8%) followed by "lack of access to them" (18.2%) and "not enough time to read them" (6.0%). Conclusion: Despite the existence and availability of evidence-based guidelines, only a minority of primary health care COPD patients in Mexico are receiving state-of-the-art treatment at the primary care level.